2016
DOI: 10.1007/s40211-016-0185-y
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported and informant-reported memory functioning and awareness in patients with mild cognitive impairment and Alzheimer´s disease

Abstract: SummaryBackgroundAwareness of subjective memory is an important factor for adequate treatment of patients with mild cognitive impairment (MCI) and Alzheimer’s disease (AD). This study served to find out whether awareness of subjective memory complies with objective performance, if differences in awareness are observed longitudinally and whether decrease of awareness can serve as a predictor of AD in MCI patients.MethodsThirty-four patients with MCI seeking help in a memory outpatient clinic were included. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 31 publications
3
13
0
2
Order By: Relevance
“…Support for this interpretation comes from a recent study in the ADNI cohort which found that anosognosia was associated with conversion from MCI to AD within 5 years (Gerretsen et al, 2017), as well as a large longitudinal study of older adults (n=2,092) which found that awareness of memory impairment begins to decline 2-3 years before dementia onset and is associated with several different types of dementia-related neuropathologies (Wilson et al, 2015). The finding of more profound anosognosia over time in the amnestic and mixed MCI subtypes is also consistent with a longitudinal study showing that increasing unawareness was related to cognitive decline over a 24 month period (Silva et al, 2016), and a cross-sectional study showing that the discrepancy between self- and informant-reported cognitive decline increased along the diagnostic continuum from cognitively normal to MCI to AD (Rattanabannakit et al, 2016). …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Support for this interpretation comes from a recent study in the ADNI cohort which found that anosognosia was associated with conversion from MCI to AD within 5 years (Gerretsen et al, 2017), as well as a large longitudinal study of older adults (n=2,092) which found that awareness of memory impairment begins to decline 2-3 years before dementia onset and is associated with several different types of dementia-related neuropathologies (Wilson et al, 2015). The finding of more profound anosognosia over time in the amnestic and mixed MCI subtypes is also consistent with a longitudinal study showing that increasing unawareness was related to cognitive decline over a 24 month period (Silva et al, 2016), and a cross-sectional study showing that the discrepancy between self- and informant-reported cognitive decline increased along the diagnostic continuum from cognitively normal to MCI to AD (Rattanabannakit et al, 2016). …”
Section: Discussionsupporting
confidence: 84%
“…The finding of more profound anosognosia over time in the amnestic and mixed MCI subtypes is also consistent with a longitudinal study showing that increasing unawareness was related to cognitive decline over a 24-month period (Silva et al, 2016), and a cross-sectional study showing that the discrepancy between self- and informant-reported cognitive decline increased along the diagnostic continuum from cognitively normal to MCI to AD (Rattanabannakit et al, 2016).…”
Section: Discussionsupporting
confidence: 78%
“…The inclusion of this score as a covariate did not significantly change the patterns of association; the self‐based memory concerns were still significantly correlated to tau in the frontal region ( data not shown ). Individuals' depressive symptoms have been shown to increase informant‐based cognitive complaints in other studies as well [15,35], but the pattern of association between informant based memory concerns and tau was not changed when GDS scores were used as a covariate ( data not shown ). It is still possible that some of the participants experienced subtle depressive symptoms that were not reflected in the GDS scores but still influenced their perceptions of their own cognitive functioning.…”
Section: Discussionmentioning
confidence: 85%
“…In addition to capturing self‐based estimates of SCD, investigators often also assess the extent of concerns about cognitive decline from an informant (spouse, child, other caregiver, or clinician). Informant‐based cognitive concerns are particularly important in the later stages of cognitive decline, when individuals' insight into their own cognitive problems diminishes and informant perceptions of cognition are more accurate [12,14,15]. In CN adults, however, self‐ and informant perceptions of cognitive decline are both predictive of future progression to MCI or AD, and the use of both measures together is a better predictor than either measure alone [5].…”
Section: Introductionmentioning
confidence: 99%
“…A longitudinal study examining individuals with incident dementia showed that, on average, awareness of memory functioning declined in the 2-3 years before dementia onset [26]. In a separate study wherein individuals with MCI and mild AD were followed for 24 months, increasing discrepancy scores between self-report and informant report regarding memory functioning were associated with declining global cognition over time [29]. Despite the overarching association between self-awareness and disease severity, it is important to note that at any given point along the continuum of MCI to moderate AD, considerable variability in awareness exists across individual patients.…”
Section: Course and Predictors Of Self-awareness In Dementiamentioning
confidence: 99%